The Safety of Dedicated-Team Catheter-Based Diagnostic Cerebral Angiography in the Era of Advanced Noninvasive Imaging - Thiex, R.; Norbash, A.M.; Frerichs, K.U. (American Journal of Neuroradiology, 2010)
BACKGROUND AND PURPOSE: Given the current high quality and usefulness of noninvasive cerebrovascular imaging, invasive angiographic evaluation of the cerebrovascular system is justified if the procedural risk for a neurologic complication is far below the anticipated benefit. The purpose of this study was to evaluate the safety of diagnostic cerebral angiography provided by a dedicated neurointerventional team in a high-volume university hospital. MATERIALS AND METHODS: A consecutive cohort of 1715 patients undergoing diagnostic cerebral angiography at our institution from 2000 to 2008 was retrospectively assessed for incidence of stroke or TIA related to cerebral angiography. In the subgroup of patients (n = 40) who serendipitously underwent DWI within the first 30 days after cerebral angiography, the presence of new DWI hyperintensities found in territories explored during angiography was tabulated. Complications related to the catheter technique and sheath placement were also studied. RESULTS: No stroke or permanent neurologic deficit was seen in any of the 1715 patients undergoing diagnostic neuroangiography. One patient experienced a TIA. Nonneurologic complications without long-term sequelae occurred in 9 patients. Two patients had punctate areas of restricted diffusion in territories that had been angiographically explored. CONCLUSIONS: Within a high-volume neurointerventional practice, the risk for neurologic complications related to catheter-based diagnostic cerebral angiography can approach zero. As the absolute number of invasive diagnostic procedures diminishes with time, diagnostic cerebral angiography remains a useful tool while providing a foundation for neuroendovascular interventions, and should preferably be performed in institutions with high-volume operators also capable of managing unanticipated complicating adverse events. CTACT angiographyDSAdigital subtraction angiographyDWIdiffusion-weighted MR imagingICAinternal carotid arteryMCAmiddle cerebral arteryMRAMR angiographyTIAtransient neurologic deficit/transient ischemic attack